(untitled) (Annals of Medical Research, 2021)
Aim: This study was planned to assess the relationship between marital adjustment and risk experienced by women during pregnancy. Materials and Methods: Women who presented to the pregnancy outpatient clinic of the hospital and were admitted to the perinatology clinic comprised the target population of the study. The sample comprised 280 (140 case and 140 control group) pregnant women. Effect size was found as 0.5 and power as 99% depending on type 1 error 0.5. This study was conducted between March and August 2016. Differences between categorical variables were compared by the Chi-square test or Fisher exact test. The Mann-Whitney U test was used to determine the differences between the median scores of the groups.Results: Three point six percent of the healthy pregnant women and 8.2% of the at-risk pregnant women had problems with their husbands. While 91.4% of the healthy pregnant women defined their happiness level as happy or very happy, this rate was 82.9% for the at-risk pregnant women (p>0.05). While the median Dyadic Adjustment Scale score of the healthy pregnant women was 56.00 (29-70), it was 53.00 (20-69) for the at-risk pregnant women. The difference between the two groups was statistically significant (p0.001). Conclusion: The at-risk pregnant women in this present study experience negative feelings about pregnancy more than did the healthy pregnant women Health professionals should be aware that pregnancy affects not only women but also all the family members. Therefore, care plans to be prepared for pregnant women should also include the family.